2023
DOI: 10.1038/s41467-023-38800-2
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-Genome Sequencing Analysis of Human Metabolome in Multi-Ethnic Populations

Elena V. Feofanova,
Michael R. Brown,
Taryn Alkis
et al.

Abstract: Circulating metabolite levels may reflect the state of the human organism in health and disease, however, the genetic architecture of metabolites is not fully understood. We have performed a whole-genome sequencing association analysis of both common and rare variants in up to 11,840 multi-ethnic participants from five studies with up to 1666 circulating metabolites. We have discovered 1985 novel variant-metabolite associations, and validated 761 locus-metabolite associations reported previously. Seventy-nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Comparison of our results to those from published studies that focused on rare variant aggregation testing of metabolite levels [14][15][16][17][18][19][20]24 (Methods) showed that 32 of the 73 identified unique genes (44%) had not been reported as significant in any of these studies. Moreover, 115 of all 192 detected gene-metabolite associations (60%) were novel (Supplementary Table 4).…”
Section: Identification and Properties Of 192 Significant Gene-metabo...mentioning
confidence: 49%
See 2 more Smart Citations
“…Comparison of our results to those from published studies that focused on rare variant aggregation testing of metabolite levels [14][15][16][17][18][19][20]24 (Methods) showed that 32 of the 73 identified unique genes (44%) had not been reported as significant in any of these studies. Moreover, 115 of all 192 detected gene-metabolite associations (60%) were novel (Supplementary Table 4).…”
Section: Identification and Properties Of 192 Significant Gene-metabo...mentioning
confidence: 49%
“…We compared our significant findings to the significant findings from eight published genetic studies of the plasma/serum or urine metabolome that focused on rare exonic variant aggregation testing and used sequencing and high-throughput metabolomics data [14][15][16][17][18][19][20]24 . We first assessed whether the genes identified in our study were reported as associated with any metabolite in any of the seven studies at their respective multiple-testing corrected significance threshold, after having mapped all gene names to their current version in Ensembl version 109 using https://www.ensembl.org/biomart/martview.…”
Section: Comparison To Previous Rare Variant Association Studies and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, large initiatives that include genetic data from diverse populations, such as the UK Biobank and the Trans-Omics for Precision Medicine (TOPMed) program, have included proteomics and metabolomics data from blood. 9 , 10 …”
Section: Main Textmentioning
confidence: 99%
“…In addition, genetic factors are strongly associated with the incidence of UGI cancer. Polygenic risk score (PRS) is constructed by incorporating numerous single nucleotide polymorphisms (SNPs), thereby reflecting an individual’s genetic susceptibility to a particular condition. This facilitates the categorization of populations into different risk strata, enabling personalized health lifestyle interventions or early disease screening. , Several studies have demonstrated that levels of certain metabolites are associated with disease genotypic risk, indicating that metabolite levels have a high heritability. , …”
Section: Introductionmentioning
confidence: 99%